2002
DOI: 10.1021/ie010887n
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Sulfation of Ca(OH)2 at Low Temperatures

Abstract: Hydrated lime [Ca(OH) 2 ] is frequently used as a sorbent in the spray-drying flue gas desulfurization (FGD) and injection/humidification FGD processes to remove SO 2 from the flue gas. In the present study, the kinetics of the reaction of Ca(OH) 2 with SO 2 has been studied by using a differential reactor and a gas mixture of N 2 , SO 2 , and H 2 O under the conditions of 0-80% relative humidity, 60-90 °C, and 1000-5000 ppm SO 2 . The reaction ceased before 1 h, and Ca(OH) 2 was incompletely converted. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 20 publications
7
65
0
Order By: Relevance
“…However, the measurements of p react described above argue against direct reaction in favor of a two-step SO 2 trapping and reaction pathway. We hope that additional measurements using molten alkali hydroxides (31) and different alkali carbonate mixtures will provide deeper insight into the balance between SO 2 residence time and reactivity as well as the possibility of a direct SO 2 → CO 2 gas-surface reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the measurements of p react described above argue against direct reaction in favor of a two-step SO 2 trapping and reaction pathway. We hope that additional measurements using molten alkali hydroxides (31) and different alkali carbonate mixtures will provide deeper insight into the balance between SO 2 residence time and reactivity as well as the possibility of a direct SO 2 → CO 2 gas-surface reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Shih et al (1999) proved that the behavior of the CO 2 reaction with Ca(OH) 2 resembled that of SO 2 in a differential reactor. On the other hand, based on the findings of Ho et al (2002) and Bausach et al (2005), SO 2 concentration contributes to the reaction rate of Ca(OH) 2 and SO 2 , and there is a mild dependency of the reaction rate on SO 2 concentration. Therefore, the effect of CO 2 concentration on the rate of reaction determines the relationship between CO 2 removal efficiency and CO 2 concentration.…”
Section: Resultsmentioning
confidence: 96%
“…For Shih et al [10] the surface coverage model was found to be the most suitable model to describe the reaction between Ca(OH) 2 and CO 2 . Ho et al [11] extended this conclusion to explain the reaction of Ca(OH) 2 sulfation. They suggested that the carbonation and sulfation of the hydrated lime are reactions controlled by chemical reaction on the surface of a grain, and the reacting surface area of the grain decreases with the deposition of solid product.…”
Section: Introductionmentioning
confidence: 90%
“…Shih et al [10] studied the reaction between Ca(OH) 2 and CO 2 ; these authors extended the study afterwards to the reaction between Ca(OH) 2 and SO 2 [11], but they selected n = 1 without any explanation. The parameters k 1 and k 2 can depend on the BET surface area (BET), temperature (T), SO 2 concentration (C SO 2 ) and relative humidity (RH).…”
Section: Modeling the Desulfurization Reactionmentioning
confidence: 99%